Bio-guided isolation of plant growth regulators from allelopathic plant-Codonopsis pilosula: phyto-selective activities and mechanisms. Issue 25 (12th April 2018) - Xie, Min; Liu, Jingkun; Yan, Zhiqiang; Li, Xiuzhuang; Yang, Xiaoyan; Jin, Hui; Su, Anxiang; Qin, Bo
Abstract : Bio-guided isolation of the aerial waste part of typical allelopathic plant- Codonopsis pilosula led to six active compounds being produced. Abstract : Natural pesticides are the subject of growing interest, as the overuse of synthetic pesticides severely threatens the safety of humans and the eco-environment. Allelopathic plants can release plentiful secondary metabolites as natural plant growth regulators to affect the growth of neighboring plants. Bio-guided isolation of the aerial waste part of typical allelopathic plant- Codonopsis pilosula led to six active compounds being produced, including ginsenoside Rg1 (1 ), ginsenoside Re (2 ), luteolin (3 ), luteolin-5- O -glucoside (4 ), ginsenoside Rb1 (5 ) and lobetyolin (6 ). Ginsenosides and luteolin-5- O -glucoside were firstly found in Codonopsis . Phyto-activity tests showed that all compounds showed inhibiting effects toward C. pilosula, and compounds2, 4, 5 and6 were also inhibitors of Amaranthus retroflexus . By contrast, the compounds promoted the seedling growth of wheat, rice and Setaria viridis . At certain concentrations, compounds1, 4, 5 and1, 2, 4 could observably promote the growth of wheat and rice seedlings, respectively, exceeding Setaria viridis . The different effects toward the two weeds might be related to the different ROS levels induced by the compounds. The ROS amounts in the root tips of S. viridis were as low as those in the control test, and the ROS content in the root tips increased with aggravation of the inhibition effect. In summary, successful isolation of phyto-selective chemicals from allelopathic plants may provide a promising method for natural herbicide screening. The compounds isolated could potentially be applied as inhibitors of dicotyledon weeds and promoters of monocotyledon crops for weed management in agriculture.